Penentuan Titik Kritis Risiko Mikrobiologi dalam Rantai Penyediaan Minuman Es di Jakarta - Irma Septiani; Caecillia Chrismie Nurwitri; Winiati P. Rahayu; Nugroho Indrotristanto (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2018)
Iced beverages are frequently consumed in Jakarta. Ironically, they have a potential to carry on pathogenic bacteria. The aim of this study was to determine the critical points of microbiological risk in iced beverages supply chain in Jakarta, which was done using the first and second principles of Hazard Analysis Critical Control Point (HACCP). The result showed that critical points (CPs) existed in every part of the supply chain: 2 CPs in home-scale ice producer, 3 CPs in factory-scale ice producer, 5 CPs in the distributor and 3 CPs in iced beverage vendor. The CPs in home-scale ice producer were water used for ice making (for producer who didn’t boil the water), water boiling process, and water filling process, whereas those in factory-scale were water used for ice making, filtration, and ice sorting process. The CPs in ice distributor line were ice transportation, storage, washing, and crushing processes. In iced beverage vendor, the CPs were ice crushing, crushed ice storage, and ingredients mixing processes. The CPs found showed the importance for producer and food safety inspector to be aware and take actions to ensure the safety of iced beverages.